Clinical and Endoscopic Characteristics of Medication Induced Esophageal Injury (Faridpur Medical College Journal, 2020)
Medications can cause several complications in the esophagus and lead to medication-induced esophageal injury. This study was carried out among patients diagnosed as medication-induced esophageal injury from June 2015 to October, 2018 in the Department of Gastroenterology, Enam Medical College and Hospital, Savar, Dhaka to investigate clinical and endoscopic characteristics of medication-induced esophageal injury as well as outcome of these patients with treatment. Patients diagnosed as malignancy, viral or fungal esophagitis, esophageal varix, corrosive and sclerotherapy induced ulcer and GERD were excluded. Clinical and endoscopic characteristics of patients diagnosed as medication-induced injury were analyzed. After given treatment, clinical improvements as well as mucosal healing of oesophageal injury were noted. Thirty seven patients were diagnosed as medication-induced esophageal injury. Their median age was 40; 17 were males and 20 were females. Common symptoms were chest pain (94.6 %), odynophagia (78.4 %) and dysphagia (62.2 %). Symptoms appeared between 3 hours to 15 hours after ingestion of medication. Predisposing factors for 75.67% of the patients were related to taking the medicine with insufficient water or in recumbent position, or both. The main causative agents were antibiotics, Non-steroidal anti-inflammatory drugs (NSAIDs) and Alendronate sodium. Common diseases that required treatment with these drugs were various urinary system diseases, osteoporosis and migraine. During endoscopy, 25 had only ulcer, 7 had only erosion and 5 had both ulcer and erosion. Most of the ulcers and erosions were located at the middle third of the oesophagus with a rate of 70%, and 58.3% respectively. Appearance of the ulcer was oval, circular, kissing and geographical shaped and their sizes vary between 6 mm to 18 mm and single or multiple in numbers. All the patients were treated with proton pump inhibitors (PPIs) or sucralfate, and the causative drugs were discontinued. Symptoms resolution occurred within 5 to 12 days after treatment and mucosal healing were detected in all patients after 4 weeks who were performed endoscopy. Almost every kind of medication, particularly doxycycline, NSAIDs can cause oesophageal ulcer and erosion. It can be successfully treated with PPIs and discontinuation of the causative medication and prevented by warning patients about drinking water sufficiently and sitting up while taking the pill.Faridpur Med. Coll. J. Jan 2019;14(1): 2-7